An Analysis of Representative and Directive Speech Acts in NIVEA’s Advertising Discourse on Instagram - Dwi Sekar Sari Kencana (PRASASTI: Journal of Linguistics, 2025)
Speech acts play a crucial role in advertisements as they serve to effectively convey messages aimed at persuading audiences to either make purchases or take specific actions related to the advertised products. This study focused on analysing the use of representative and directive speech acts in advertisements by NIVEA Indonesia on its official Instagram account, @Nivea_id, during the period from January to June 2024. The research employed a descriptive qualitative approach to analyse the data, applying Searle’s (1979) speech act theory as the framework. The data comprised sentences found in Instagram captions that demonstrate representative and directive speech acts. The findings revealed that NIVEA utilizes both types of speech acts in promoting its products. Representative speech acts were employed to provide information, make assertions, and present claims, effectively describing the products and persuading readers to purchase and use them. Meanwhile, directive speech acts were utilized to encourage action, either directly or indirectly, through commands, suggestions, invitations, and advice, all aimed at motivating readers to buy and engage with the products.